Plumericin inhibits the viability of cervical cancer cells by induction of apoptosis through degradation of DNA structure (Bangladesh Journal of Pharmacology, 2016)
The current study demonstrates the effect of plumericin on the viability and induction of apoptosis through degradation of double helical DNA structure in Bu25TK and HeLa cervical carcinoma cell lines. Plumericin treatment exhibited concentration- and time-dependent effect on the viability of Bu25TK and HeLa cells. Incubation of Bu25TK and HeLa cells with 40 µM concentration of plumericin decreased cell viability to 24 and 29%, respectively after 48 hours. Plumericin treatment also caused significant increase in the proportion of apoptotic cells in both the cell lines at 40 µM concentration compared to the control cells. Examination of the DNA double helical structure after 48 hours of treatment with plumericin at 40 µM concentration showed DNA degradation and formation of comets. Thus, plumericin exhibits inhibitory effect on the viability of Bu25TK and HeLa cells and induced apoptosis through DNA degradation. Therefore, plumericin is a potent candidate for the treatment of cervical carcinoma.